Analysis of the Influence of Good Corporate Governance on Financial Performance of Textile and Garment Subsector Companies Listed on the Indonesia Stock Exchange from 2022 to 2024 - Afriana, Wendra; Darmawati, Sri Sapto; Mulyani, Sulistining Tri; Mulatsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This research seeks to evaluate how the board of directors, independent commissioners, and audit committees affect the financial performance of textile and apparel firms listed on the Indonesia Stock Exchange (IDX) throughout the 2022–2024 period. Data for the analysis were sourced from the official IDX portal (www.idx.co.id). The study designates independent commissioners, audit committees, and institutional ownership as independent variables, while the dependent variable is the firms’ financial performance, represented by the Return on Assets (ROA) indicator. The sample was determined using a purposive sampling technique, yielding 13 firms and 39 observations from the textile and apparel sector that met the established research criteria. Data processing involved classical assumption tests, followed by multiple linear regression analysis performed with SPSS version 31. The results reveal that independent commissioners, audit committees, and institutional ownership have impacts on the firms’ financial performance.